The Impact of Principal Leadership Style, Organizational Culture, Teacher Motivation, and Work Discipline on School Effectiveness - Mochamad Irfan; Istiarsyah; Gamar Al Haddar; Sederhana Zai (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the impact of principal leadership style, organizational culture, teacher motivation, and work discipline on school effectiveness. Using a quantitative approach with an explanatory research design, data were collected through a structured questionnaire distributed to 200 teachers in primary and secondary schools in West Bandung Regency, Indonesia. The data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results reveal that principal leadership style, organizational culture, teacher motivation, and work discipline all have positive and significant effects on school effectiveness, both partially and simultaneously. Among these variables, teacher motivation is identified as the most influential factor in improving school effectiveness. The coefficient of determination indicates that 61.1% of the variance in school effectiveness is explained by the four independent variables, while the remaining 38.9% is influenced by other factors. These findings highlight the importance of adopting an integrated management approach that emphasizes effective leadership, a strong organizational culture, high teacher motivation, and disciplined work practices to enhance school performance. The study provides practical implications for school leaders and policymakers in developing strategies to improve educational quality and institutional effectiveness.